2019
DOI: 10.1136/bcr-2019-232618
|View full text |Cite
|
Sign up to set email alerts
|

Extrapulmonary sarcoidosis primarily presenting as cholestatic liver disease

Abstract: Sarcoidosis is a multisystem inflammatory disorder associated with non-caseating granulomas in affected organs, most commonly the lungs. Involvement of extrapulmonary organs is common, but lack of pulmonary involvement is rare and is called non-pulmonary sarcoidosis (NPS). Like pulmonary sarcoidosis, a definitive diagnostic test for NPS does not exist. Instead, the diagnosis of sarcoidosis requires the following elements: clinical and radiographic manifestations of sarcoidosis, histopathological detection of n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 36 publications
(37 reference statements)
0
4
0
Order By: Relevance
“…Intrahepatic sarcoidosis can resemble primary sclerosing cholangitis (PSC) or in rare circumstances these two entities can coexist. 8–12 …”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…Intrahepatic sarcoidosis can resemble primary sclerosing cholangitis (PSC) or in rare circumstances these two entities can coexist. 8–12 …”
Section: Introductionmentioning
confidence: 80%
“…Intrahepatic sarcoidosis can resemble primary sclerosing cholangitis (PSC) or in rare circumstances these two entities can coexist. [8][9][10][11][12] We present a case report of a patient with radiological findings 'typical' for PSC and liver biopsy showed non-caseating granulomas consistent with hepatic sarcoidosis.…”
Section: Introductionmentioning
confidence: 99%
“… 9 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 The dosage of corticosteroids, particularly prednisolone, varies from 20 mg to 60 mg per day. 12 , 27 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 In our review, some of the studies used dosages of 0.5 mg to 1 mg/kg/day, 45 , 46 , 47 and none of the studies reported a prednisolone dose of greater than 1 mg/kg/day. Two review articles suggested a time frame of 4–6 weeks for initial duration of treatment, and subsequently to taper off prednisolone 5‐10 mg every 4–8 weeks.…”
Section: Discussionmentioning
confidence: 96%
“…The indication for therapy has been based on the presence of symptoms and biochemical liver derangement, with or without evidence of fibrosis/ cirrhosis on imaging 9,27–36 . The dosage of corticosteroids, particularly prednisolone, varies from 20 mg to 60 mg per day 12,27,37–44 . In our review, some of the studies used dosages of 0.5 mg to 1 mg/kg/day, 45–47 and none of the studies reported a prednisolone dose of greater than 1 mg/kg/day.…”
Section: Discussionmentioning
confidence: 99%